Rationale, design, and methodology of My Body Is Fit and Fabulous at school (MyBFF@school) study: a multi-pronged intervention program to combat obesity among Malaysian schoolchildren - Abdul Halim Mokhtar; Ruziana Mona Wan Mohd Zin; Abqariyah Yahya; Fuziah Md. Zain; Rusidah Selamat; Zahari Ishak; Muhammad Yazid Jalaludin (BMC Public Health)
Abstract Background Childhood obesity has increased rapidly in recent years and is now a global epidemic. To combat this, MyBFF@school program, a multi-faceted obesity intervention incorporating physical activity in the form of small-sided games (SSG), nutrition, and psychology components for schoolchildren was designed. This paper is aimed at describing the protocol of the MyBFF@school program and presenting the baseline findings including the overweight and obesity prevalence. Methods MyBFF@school is a school-based, cluster randomized controlled trial (C-RCT) study. The investigators selected government schools from Federal Territory of Kuala Lumpur, Selangor and Negeri Sembilan by stratified proportionate random sampling based on the multi-ethnic population and the urban–rural location of schools. Subsequently, the schools were assigned randomly to intervention and control groups. The intervention schools underwent MyBFF@school program, whereas the control followed standard school curriculum for a duration of six months. The intervention modules replaced the existing two physical education classes and one co-curriculum activity per week. Three assessments i.e. at baseline, month-3 and month-6 were conducted. Anthropometric, clinical examination, blood, physical fitness, nutrition, and psychology parameters were collected. Results Twenty-three out of 1,196 primary schools (seven interventions and 16 controls) and 15 out of 416 secondary schools (six interventions and nine controls). The investigators screened 11,950 primary (age 9–11 years) and 10,866 secondary (age 13, 14, 16 years) schoolchildren. The investigators found 3,516 primary schoolchildren (29.4%) and 2,910 secondary schoolchildren (26.8%) had BMI z-score of more than + 1SD who were eligible for the study. Of these, 39.7% (N = 1397) of the primary and 35.8% (N = 1041) of the secondary schoolchildren agreed to participate in the study. The mean (SD) characteristics for the participating primary and secondary schoolchildren were: BMI z-score, + 2.29 (± 0.81) and + 2.10 (± 0.71); waist circumference, 75.06 (± 9.6) cm and 85.5 (± 10.9) cm; percentage body fat, 37.8% (± 6.5%) and 39.2% (± 7.3%); and muscle mass, 14.7 (± 2.9) and 23.1 (± 5.2) kg respectively. Conclusion MyBFF@school program, a school-based multi-pronged intervention was designed to combat childhood obesity. Screening of 22,816 primary and secondary schoolchildren found 29.4% of primary schoolchildren and 26.8% of secondary schoolchildren to be overweight and obese which reflected the urgency for an effective intervention. Trial registration Clinical trial number: NCT04155255, November 7, 2019 (Retrospective registered). National Medical Research Register: NMRR-13–439-16563. Registered July 23, 2013. The intervention program was approved by the Medical Research and Ethics Committee (MREC), Ministry of Health Malaysia and Educational Planning and Research Division (EPRD), Ministry of Education Malaysia. It was funded by the Ministry of Health Malaysia.